MEN’S BODY RELATED PRACTICES AND MEANINGS OF MASCULINITY - Dewing, Sarah; Foster , Don (PINS-Psychology in Society, 2025)
The present investigation is about men and their bodies. Against the increasing visibility of the (idealised and eroticized) male body in Western popular culture as well as claims that men are becoming the new victims of “the beauty myth”, this study aims to examine men’s appearance related practices in relation to meanings of masculinity. Semi-structured, in depth interviews were conducted with fifteen men between the ages of 18 and 38. Using that method of discursive analysis developed specifically for the investigation of masculinities by Wetherell & Edley (1999), various subject positions taken up by the men in talking about their appearance related practices were identified. The men positioned themselves as unconcerned with appearance, untraditionally masculine, heterosexual, well-balanced and disembodied. A concern for appearance appears inconsistent with ideals of hegemonic masculinity (as valued by these men), and it is suggested that men are unlikely to constitute a large proportion of those individuals who might be described as “victims” of “the beauty myth”.